How Similar are Human Mesenchymal Stem Cells Derived from Different Origins? A Review of Comparative Studies - Farkhad, Najmeh K.; Mahmoudi, Ali; Mahdipour, Elahe (Current Stem Cell Research & Therapy, 2021)
Mesenchymal stem/stromal cells (MSCs) are adult multipotent cells with self-renewal potential and the ability to differentiate into specialized cells. MSCs home in various tissues and can be isolated using simple methods. Because of this feasibility in the isolation and culture of MSCs in vitro, many scientists have focused on the therapeutic applications of MSCs for various diseases and conditions. The selection of the tissue source to obtain MSCs mainly depends on the availability of the tissue, the patient’s health status, as well as the expertise of the researcher. However, some studies indicate that MSCs derived from different tissue sources are not the same and possess different regenerative capacities. Therefore, in this review, we have collected and summarized the results from studies that have performed head-to-head comparisons between MSCs isolated from different tissues. Despite the assessment method discrepancy between studies, results from these studies reveal that MSCs derived from different tissue sources are not the same. Some such as umbilical cord-derived MSCs and menstrual blood-derived MSCs were identified with robust angiogenic potentials. However, cord blood-derived MSCs possessed a strong cartilage repair capacity. Further investigations are required to establish certain capabilities for MSCs derived from a particular tissue origin. Nevertheless, it is recommended to consider the possibility of functional variations between MSCs isolated from distinct tissue origins when applying MSCs in clinics.
Keywords: stem cell profiling